2013
DOI: 10.1155/2013/865159
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of 4-1BB and 4-1BBL Interaction Reduces Obesity-Induced Skeletal Muscle Inflammation

Abstract: Obesity-induced skeletal muscle inflammation is characterized by increased macrophage infiltration and inflammatory cytokine production. In this study, we investigated whether 4-1BB, a member of the TNF receptor superfamily (TNFRSF9) that provides inflammatory signals, participates in obesity-induced skeletal muscle inflammation. Expression of the 4-1BB gene, accompanied by increased levels of inflammatory cytokines, was markedly upregulated in the skeletal muscle of obese mice fed a high-fat diet, in muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Skeletal muscle transcript and protein levels of F4/80 and CD68, which were higher in the HFD-fed mice than in the RD-fed mice, were also reduced by quercetin in a dose-dependent manner (Figures 1(c) and 1(d) ). Subsequently, we examined the effect of quercetin on inflammatory receptors such as TNF receptor superfamily member 9 (4-1BB) and toll-like receptor 4 (TLR4), which are known to promote obesity-induced inflammatory responses in skeletal muscle [ 17 , 18 ]. Transcript levels of the inflammatory receptors were lower in the skeletal muscle of the HFD/Q0.05- and HFD/Q0.1-fed mice than in that of the HFD-fed mice ( Figure 1(e) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle transcript and protein levels of F4/80 and CD68, which were higher in the HFD-fed mice than in the RD-fed mice, were also reduced by quercetin in a dose-dependent manner (Figures 1(c) and 1(d) ). Subsequently, we examined the effect of quercetin on inflammatory receptors such as TNF receptor superfamily member 9 (4-1BB) and toll-like receptor 4 (TLR4), which are known to promote obesity-induced inflammatory responses in skeletal muscle [ 17 , 18 ]. Transcript levels of the inflammatory receptors were lower in the skeletal muscle of the HFD/Q0.05- and HFD/Q0.1-fed mice than in that of the HFD-fed mice ( Figure 1(e) ).…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that quercetin supplementation markedly reduced transcript and protein levels of the macrophage-specific markers CD68 and F4/80 in the skeletal muscle of HFD-fed obese mice, indicating that it prevented macrophage accumulation, which is in line with our in vitro observation that inhibits the chemotactic activity of macrophages [ 13 ]. Thus, the reduced macrophage infiltration by quercetin may decrease the cross-talk between macrophages/muscle cells, which promotes their inflammatory responses [ 7 , 17 ], and this may be favorable for the reduction of skeletal muscle inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-induced inflammation increases the risk for development of metabolic complications such as insulin resistance, type 2 diabetes and neurodegenerative diseases. Obesity-induced inflammation initially occurs in metabolically active peripheral organs (e.g., adipose tissue, liver, and skeletal muscle) [1][2][3][4][5]. For example, under obese/diabetic conditions, adipose tissue releases free fatty acid (FFA) and various secretory proteins, including inflammatory cytokines such as TNFa, IL-6, and MCP-1, which then play a crucial role by promoting macrophage infiltration and activation, leading to chronic low-grade systemic inflammation [6][7][8].…”
Section: Abstract: Astrocyte; Hypothalamus; Inflammation; Obesitymentioning
confidence: 99%
“…Obesity-induced inflammation initially occurs in metabolically active peripheral organs (e.g., adipose tissue, liver, and skeletal muscle) [1][2][3][4][5]. Obesity-induced inflammation initially occurs in metabolically active peripheral organs (e.g., adipose tissue, liver, and skeletal muscle) [1][2][3][4][5].…”
mentioning
confidence: 99%
“…Hence, it is conceivable that 4-1BB/4-1BBL may participate in glial cell-mediated hypothalamic inflammation. Of note, our previous study demonstrated that 4-1BB and/or 4-1BBL enhance obesity-induced peripheral inflammation such as adipose tissue (adipocytes/macrophages) and skeletal muscle (myotubes/macrophages) by providing a bidirectional inflammatory signal [17,19]. However, the association of these molecules with obesityinduced hypothalamic inflammation remains completely unknown.…”
mentioning
confidence: 98%